13.8k views
1 vote
Solve the following system using the Substitution method:

x - y = -4
x - 2y = -6
(3 points, 2 for work, 0.5 for each part of the solution (x,y))

User Erik Baars
by
5.4k points

1 Answer

6 votes

Answer:

(x, y) = (-2, 2)

Explanation:

We are given the following two equations which we are to solve using the substitution method:


x - y = -4 --- (1)


x - 2y = -6 --- (2)

From equation (1):


x = y-4

Substituting this value of x in (2) to get:


x = [tex]x - 2y = -6\\\\(y-4)-2y=-6\\\\-y=-6+4\\\\-y=-2[/tex]

y = 2

Substituting the value of y in (1) to get x:


x - y = -4


x - 2 = -4


x = -4 + 2

x = -2

Therefore, (x, y) = (-2, 2).

User GreenOwl
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.